Loss of ganglioglomerular nerve input to the carotid body impacts the hypoxic ventilatory response in freely-moving rats - Getsy, Paulina M.; Coffee, Gregory A.; Lewis, Stephen J. (Frontiers in Physiology, 2023)
The carotid bodies are the primary sensors of blood pH, pO2 and pCO2. The ganglioglomerular nerve (GGN) provides post-ganglionic sympathetic nerve input to the carotid bodies, however the physiological relevance of this innervation is still unclear. The main objective of this study was to determine how the absence of the GGN influences the hypoxic ventilatory response in juvenile rats. As such, we determined the ventilatory responses that occur during and following five successive episodes of hypoxic gas challenge (HXC, 10% O2, 90% N2), each separated by 15 min of room-air, in juvenile (P25) sham-operated (SHAM) male Sprague Dawley rats and in those with bilateral transection of the ganglioglomerular nerves (GGNX). The key findings were that (1) resting ventilatory parameters were similar in SHAM and GGNX rats, (2) the initial changes in frequency of breathing, tidal volume, minute ventilation, inspiratory time, peak inspiratory and expiratory flows, inspiratory and expiratory drives were markedly different in GGNX rats, (3) the initial changes in expiratory time, relaxation time, end inspiratory or expiratory pauses, apneic pause and non-eupneic breathing index (NEBI) were similar in SHAM and GGNX rats, (4) the plateau phases obtained during each HXC were in general similar in SHAM and GGNX rats, and (5) the ventilatory responses that occurred upon return to room-air were in general similar in SHAM and GGNX rats. Overall, these changes in ventilation during and following HXC in GGNX rats raises the possibility the loss of GGN input to the carotid bodies effects how primary glomus cells respond to hypoxia and the return to room-air.